Molecular and morphological analyses of avian eggshell excavated from a late thirteenth century earth oven - Oskam, C.; Jacomb, C.; Allentoft, M.; Walter, R.; Scofield, R.; Haile, James; Holdaway, R.; Bunce, Michael (Academic Press, 2011)
Using ancient DNA (aDNA) extracted from eggshell of the extinct moa (Aves: Dinornithiformes) wedetermined the species composition and number of eggs found in a late thirteenth century earth ovenfeature at Wairau Bar (South Island, New Zealand) e one of New Zealand’s most significant archaeologicalsites. Mitochondrial and nuclear DNA signatures confirmed this oven feature contained fragmentsof at least 31 moa eggs, representing three moa genera: Emeus; Euryapteryx; Dinornis. We demonstratethrough the genetic identification of 127 moa eggshell fragments that thickness is an unreliable characterfor species assignment. We also present a protocol for assessing the preservation likelihood of DNA inburnt eggshell. This is useful because eggshell fragments found in archaeological contexts have oftenbeen thermally modified, and heat significantly increases DNA fragmentation. Eggshell is widely used inradiocarbon dating and stable isotope research, this study showcases how aDNA can also add to ourknowledge of eggshell in both archaeological and palaeoecological contexts.